Histopathological changes of acetaminophen-induced liver injury and subsequent liver regeneration in BALB/C and ICR mice - Fazil, Muhammad Azam; Saulol Hamid, Nur Fazila; Raslam, Nurul Ain Fatin; Mohamed Mustapha, Noordin; Degu, Nurhusien Yimer (Veterinary World, 2019)
Background and Aim: Laboratory mice are widely used as a research model to provide insights into toxicological studies of various xenobiotic. Acetaminophen (APAP) is an antipyretic and analgesic drug that is commonly known as paracetamol, an ideal hepatotoxicant to exhibit centrilobular necrosis in laboratory mice to resemble humans. However, assessment of histopathological changes between mouse strains is important to decide the optimal mouse model used in APAP toxicity study. Therefore, we aim to assess the histomorphological features of APAP-induced liver injury (AILI) in BALB/C and Institute of Cancer Research (ICR) mice. Materials and Methods: Twenty-five ICR mice and 20 BALB/C mice were used with five animals as controls and the rest were randomly divided into three time points at 5, 24, and 48 hours post-dosing (hpd). They were induced with 500 mg/kg APAP intraperitoneally. Liver sections were processed for hematoxylin-eosin staining and histopathological changes were scored based on grading methods. Results: Intense centrilobular damage was observed as early as 5 hpd in BALB/C as compared to ICR mice, which was observed at 10 hpd. The difference of liver injury between ICR and BALB/C mice is due to dissimilarity in the genetic line-up that related to different elimination pathways of APAP toxicity. However, at 24 hpd, the damage was markedly subsided and liver regeneration had taken place for both ICR and BALB/C groups with evidence of mitotic figures. This study showed that normal liver architecture was restored after the clearance of toxic insult. Conclusion: AILI was exhibited earlier in BALB/C than ICR mice but both underwent liver recovery at later time points.